Examining the factors influence bond market performance in Malaysia / Muhammad Syukri Mohd Jefri - Mohd Jefri, Muhammad Syukri (Faculty of Business and Management, 2018)
This study investigates the factors that influence bond market performance in Malaysia by analyzing the relationship between bond market performance that is measured by government bond price 10Y (BP), maturity of bond (N), interest rates (R), inflation rate (I) and bond yields (YTM). This study covers the Malaysian bond market in which Malaysia government decides to make the bonds as priority in the market and become the main sources for long term financing due to the Asian financial crisis that has been occurred in year 1997 (Fabella & Madhur, 2003). Besides, this study chose Malaysian government bond as the financial data from the year 2010 to 2017 were used 32 observations for this study. A multiple linear regression analysis was executed in this study to see the relationship between dependent and independent variables. The dependent variable is bond market performance and is measured by government bond 10Y price (BP), whereas the independent variables are maturity of bond (N), interest rate (R), inflation rate (I) and bond yield (YTM). As a result this study found inflation rate (I) and bond yield (YTM) have significant positive and the other one which is at significant negative impact on bond market performance while maturity of bond (N) and interest rates (R) both has positive and insignificant effect on bond market performance.